Rancang Bangun Sistem Informasi Pengelolaan Surat Berbasis Web (Studi Kasus: Kelurahan Jatiasih) - Mawar Anggraini Prabowo; Eko Aziz Apriadi; Ribut Julianto; Agus Komarudin (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2026)
This study aims to design and develop a web-based information system for managing incoming and outgoing correspondence at the Jatiasih Urban Village Office. The main problem faced is that correspondence recording is still carried out manually using a logbook, which may lead to data loss, difficulty in retrieving archives, delays in document management, and disorganized record keeping. The system development method used in this study is the waterfall model, which consists of requirements analysis, system design, implementation, and testing stages. The system was developed using the PHP programming language and MySQL database to support integrated processes for recording, storing, searching, managing, and reporting correspondence data. System testing was conducted using the black-box testing method on eight main functions, including admin login, incoming letter input, outgoing letter input, letter data editing, letter data deletion, letter file uploading, incoming letter report printing, and outgoing letter report printing. The test results show that all functions operate according to user requirements, with a success rate of 100%. Therefore, the developed information system can help make correspondence management at the Jatiasih Urban Village Office more structured, faster, more accurate, and more efficient.